PENGARUH IKLAN LAYANAN MASYARAKAT TERHADAP SIKAP PELAJAR KOTA BATAM MENGENAI INFORMASI HOAX DI MEDIA SOSIAL (Studi Pada Iklan Lawan Berita Hoax TransTV) - Arif, Shinta Oktavia Putri; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2019)
This study discusses "The Effect of Public Service Advertisements on Student Attitudes in the City of Batam Regarding Hoax Information on Social Media (Study on TransTV Hoax News Opponent Ads). This research was conducted with the aim to examine the effect of public service advertising on attitudes. The sampling technique uses Simple Random sampling. Data collection techniques used in this study were questionnaires. Based on the testing of the instrument it can be stated that all the questions used are valid (r count> 0.099) and reliable (Alpha> 0.6). The results of the value of the coefficient of determination is 0.297 which means that 29.7% of the variation in changes that occur in the attitude of Batam City students regarding hoax information on social media. While the remaining 70.3% is influenced by other variables not included in the research model. The results of the t test show, t count (12,887) ˃ t table (1,966) with a significance value of 0,000 <0,05. It can be concluded that public service ads have a positive and significant effect on the attitude of Batam City students regarding hoax information on social media (studies on adverts against TransTV hoax news).